노인의 사회적 존중에 대한 주관적 인식이 우울에 미치는 영향: 사회·문화 활동 만족도와 정책 영향력 인식의 매개효과 - 김은경(Eun-Kyung Kim) (한국콘텐츠학회 논문지, 24(1), 2024)
본 연구는 2020년 노인실태 조사를 활용하여 노인의 사회적 존중에 대한 주관적 인식이 우울에 미치는 영향 관계뿐만 아니라 사회·문화 활동 만족도와 정책 영향력 인식이 우울에 미치는 영향 관계를 Baron과 Kenny의 매개효과 분석으로 알아보았다. 연구 결과 노인의 사회적 존중에 대한 주관적 인식은 우울에 유의미한 부적 영향 관계를 나타내어 노인이 사회에서 존중받고 있다고 느낄수록 우울이 낮아졌다(p< .001). 또한 노인의 사회 존중에 대한 주관적 인식은 사회·문화 활동 만족도와 정책 영향력 인식에 정적 영향 관계를 보였고 사회·문화 활동 만족도와 정책 영향력 인식은 우울에 부적 영향 관계를 나타냈다(p< .001). 따라서 사회에서 노인들이 우울하지 않기 위해서는 사회·문화 활동을 통한 세대 통합적 사회 존중이 이루어지도록 힘써야 하며 노인이 민주적이고 성숙한 시민으로서 정부 정책에 영향을 미칠 수 있도록 교육과 더불어 사회통합의 정책 실천을 위한 환경이 조성되어야 할 것이다. Based on a survey on older adults in 2020, this study used Baron and Kenny’s mediation effect to explore the relationship between the subjective perception of social respect among older adults on depression and the relationship between satisfaction with sociocultural activities and perception of policy influence on depression. The results demonstrated that subjective perception of social respect of older adults had a significant negative relationship with depression, which means that the more the older adults felt respected by society, the lower will be their depression(p< .001). In addition, the older adults’ subjective perception of social respect showed a positive relationship with satisfaction with sociocultural activities and perception of policy influence. Satisfaction with sociocultural activities and perception of policy influence showed a negative relationship with depression (p< .001). Therefore, for older adults in society not to be depressed, efforts should be made to ensure generational integration and social respect through social and cultural activities. Furthermore, an environment for implementing social integration policies along with education is required to ensure that older adults can influence policies as democratic and mature citizens. KCI Citation Count: 0